2017
DOI: 10.15420/ecr.2016:32:1
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease in Women: Understanding Symptoms and Risk Factors

Abstract: Despite men and women sharing classic cardiovascular risk factors, the relative importance of each risk factor may be gender specific.For example, the deleterious impact of smoking is greater in women Abstract Cardiovascular disease (CVD) in women remains under-diagnosed and undertreated due to the diagnostic challenge it presents, as well as the persisting attitude that CVD predominantly affects men. Gender-related risk factors have now been identified but there is a lack of clinical application, leading to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 45 publications
3
62
0
1
Order By: Relevance
“…Furthermore, this study explores a different set of informative risk factors for males and females HF patients to predict their survival. Our findings are consistent with some other studies [6, 32]. It is possible to question the generalizability of our findings because the data is collected from only two main hospitals of Faisalabad.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, this study explores a different set of informative risk factors for males and females HF patients to predict their survival. Our findings are consistent with some other studies [6, 32]. It is possible to question the generalizability of our findings because the data is collected from only two main hospitals of Faisalabad.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, previous studies have showed that breast cancer survivors treated with chemo- and/or radiotherapy may develop systolic cardiac dysfunction or cardiovascular disease (CVD) up to 10 years after diagnosis [ [3] , [4] , [5] , [6] , [7] ]. In women, such dysfunction often has a vague onset that can lead to undertreatment [ 8 ]. Long-term breast cancer survivors are also at a higher odds of depressive and anxiety symptoms than their peers with no history of cancer [ [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, preventive care including counseling and prophylactic treatment is less likely to be offered to women than men with similar atherosclerotic cardiovascular disease risk ( 87 , 89 ), while medical management of these patients tends to be less vigorous, thus more rarely achieving optimal results ( 90 , 91 ). While most cardiovascular risk factors in women overlap with those in men, several circumstances remain characteristic of women ( 92 , 93 ), as it can be seen outlined in Figure 2 .…”
Section: Cardiovascular Disease In Pcosmentioning
confidence: 99%